O instinto, a paixão e suas nuanças : um estudo sobre o papel da sexualidade no desenvolvimento da sociabilidade em Jean-Jacques Rousseau - Ferreira Junior, Paulo (2015)
In the present study the aim is to investigate the role of sexuality in the development of sociability in Jean-Jacques Rousseau. This research works in two contexts. The first comprises the denaturation of man in general and the general formation of societies; in this case, the works that support this reading are: Discourse on the Origin of Inequality, Essay on the Origin of Languages, Social Contract and Fragment of the Climates Influence on the Civilization. The second context comprises the education of the man from nature prepared to live in any kind of society. In this case, the work that supports this reading is Emilio, or On education. In both, first or second context, the socialization process of specie and the development of sociability in the individual can be divided into distinct stages in which sexuality acts, alternately, in the nuances that separate these stages. By their specific character, the sexual need allows a way to understanding the relationship between the instinct and the genesis of passions. In this context, the sexuality operates as a kind of catalyst for social potentialities that places the society in the horizon of man as a possible way of collective survival or as a specific destination of specie. In short, the sexuality is a little studied topic in Rousseau; however, it is a possible interpretation key to understanding how the man, who was not social by nature, found the sociability as a proper element to their nature.